Knowledge, attitude, and perception of women towards medical versus surgical management of abnormal uterine bleeding: A cross-sectional descriptive study. - Chandrika, Dr.Volukula Poorna Pranitha; Manasa, Dr.Tekupudi; Hasamnis, Dr. Varada A. (Student's Journal of Health Research Africa, 2025)
Background: Abnormal uterine bleeding (AUB) significantly affects the quality of life in reproductive-age women. Despite the availability of both medical and surgical treatments, decision-making is often influenced by inadequate awareness and socio-cultural perceptions. Objectives: To assess the knowledge, attitudes, and perceptions of women diagnosed with AUB regarding its medical and surgical management, and to evaluate their treatment preferences, concerns, and adherence. Methods: A cross-sectional descriptive study was conducted at the gynecology outpatient department of KIMS & RF, Amalapuram, Andhra Pradesh, from November 2024 to February 2025. A total of 136 women with diagnosed AUB were enrolled. Data were collected using a structured and validated questionnaire covering sociodemographic characteristics, awareness levels, treatment attitudes, and decision-making behavior. Statistical analysis was performed using SPSS, with significance assessed via chi-square tests. Results: Of the 136 participants, the majority (66.2%) were aged 31–50 years and predominantly married (77.2%). Awareness of AUB was high (94.1%), but only 66.2% were aware of both medical and surgical options. While 89.7% had a favorable view of surgical management, 66.2% preferred medical treatment, and 29.4% chose a combination approach. Treatment refusal was reported by 29.4%, primarily due to fear of surgery. Education was significantly associated with treatment preference (p = 0.044), and diagnosis with AUB was significantly associated with adherence (p < 0.001). Occupation influenced refusal of recommended management (p = 0.0165). Conclusion: Despite high awareness of AUB, significant gaps exist in understanding treatment modalities. Cultural fears and misconceptions continue to influence patient decisions. Patient-specific counseling is imperative to improve informed decision-making and treatment compliance. Recommendations: Integrate routine counseling addressing both treatment options, dispel misconceptions, enhance shared decision-making, and prioritize health education interventions during gynecological consultations for AUB.